2003
DOI: 10.1007/s00455-003-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Paralysis: Distinguishing Xth Nerve from Recurrent Nerve Paralysis Through Videoendoscopic Swallowing Study (VESS)

Abstract: Distinction between unilateral recurrent laryngeal nerve paralysis and Xth nerve paralysis is a rarely addressed issue in the literature. However, it may be crucial to examine the cause of the paralysis and to perform the appropriate investigation. The videoendoscopic swallowing study has been demonstrated to be a useful tool in assessing pharyngeal function. Since in unilateral Xth nerve paralysis the pharynx is impaired on the same side as the vocal fold immobility, it may be easily detected by videoendoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 28 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Although it was reported that the pharyngeal branch of the vagus nerve plays a major role in elevating the larynx (5), the RLN also may be involved in this movement. Some clinical reports noted that isolated RLN paralysis rarely affects bolus residue or saliva pooling in the pyriform sinus just above the UES (12,24), so isolated RLN damage may have less influence on the pharyngeal function during swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was reported that the pharyngeal branch of the vagus nerve plays a major role in elevating the larynx (5), the RLN also may be involved in this movement. Some clinical reports noted that isolated RLN paralysis rarely affects bolus residue or saliva pooling in the pyriform sinus just above the UES (12,24), so isolated RLN damage may have less influence on the pharyngeal function during swallowing.…”
Section: Discussionmentioning
confidence: 99%